Neighborhood variation in early adult educational outcomes: The case of Norway - Nordvik, Viggo; Galster, George (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Individuals originating in different neighborhoods fare differently in later life. Part of this is because families sort non-randomly over the urban landscape; different types of families live in systematically different neighborhoods. Another part of the explanation is that children in different neighborhoods are exposed to different urban opportunity structures. The opportunity structure can exert its influence through social interactive, environmental and institutional factors. Using a multi-level framework applied to a Norwegian register-based data set with complete coverage of 1986-1992 cohorts with siblings, we decompose the variation in high school completion and in enrollment in higher education at age 22 into variances at the levels of family and neighborhood occupied at age seven. The variations in both outcome variables among young adults raised in different neighborhoods are substantively important. The gap in expected high school completion rates between children raised in the upper and lower quartiles of the neighborhood distribution is eleven percentage-points; the equivalent gap in being enrolled in higher education is 16 percentage points. We also find substantial heterogeneity in this neighborhood variation; for example, boys are more vulnerable to neighborhood variations, while children residing with both parents at the age of seven are less vulnerable. We argue that the large variation across neighborhoods in educational outcomes of young adults should be of concern for policymakers. It can both imply a suboptimal utilization of human resources and it can feed into inequalities later on in the lifecourse and harm social cohesion thereby.